2012
DOI: 10.1128/jvi.06463-11
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against Extracellular Exposure of a Highly Immunogenic Region in the C-Terminal Domain of the Simian Immunodeficiency Virus gp41 Transmembrane Protein

Abstract: The generally accepted model for human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein topology includes a single membrane-spanning domain. An alternate model has been proposed which features multiple membrane-spanning domains. Consistent with the alternate model, a high percentage of HIV-1-infected individuals produce unusually robust antibody responses to a region of envelope, the so-called "Kennedy epitope," that in the conventional model should be in the cytoplasm. Here we show analogous, robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
(77 reference statements)
2
22
1
Order By: Relevance
“…hVLPs also showed no binding with an antibody to the Kennedy epitope of the CTT, Chessie 8, in agreement with a prior report that this epitope is generally not exposed on virions ( Fig. 2B) (40,41).…”
supporting
confidence: 91%
“…hVLPs also showed no binding with an antibody to the Kennedy epitope of the CTT, Chessie 8, in agreement with a prior report that this epitope is generally not exposed on virions ( Fig. 2B) (40,41).…”
supporting
confidence: 91%
“…These cellular results are in contrast to a study using GFP-fused gp41 truncation mutants where gp41 CTT was only observed in a cytoplasmic orientation in Env-expressing cells [35]. More recently, Desrosiers and colleagues have observed apparent exposure of CTT sequences on the surface of Env-expressing cells [36]. However, their results suggested that apparent CTT exposure was due to “shedding” of Env from expressing cells that subsequently bound to the surface of non-expressing cells and not that the CTT was natively exposed [36].…”
Section: Introductioncontrasting
confidence: 80%
“…More recently, Desrosiers and colleagues have observed apparent exposure of CTT sequences on the surface of Env-expressing cells [36]. However, their results suggested that apparent CTT exposure was due to “shedding” of Env from expressing cells that subsequently bound to the surface of non-expressing cells and not that the CTT was natively exposed [36]. Attempts to interpret and condense the results of these studies into a topological model for the CTT are hindered by the limitations of the differing techniques used by each group to determine CTT topology.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, the existence of neutralizing antibodies directed against the so-called Kennedy epitope of HIV-1 has been used as an argument supporting a topology switch of the (much larger) gp41 cytosolic tail [18][20]. The same issue has additionally been discussed in connection with the cytosolic tail of SIV gp41 and put in relation with other known cases [21].…”
Section: Discussionmentioning
confidence: 99%